The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0103-84782013001100004
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils on the control of stem and ear rot in maize

Abstract: Stem and ear rot caused by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Extensive structural SEM time‐course analysis of early infection steps has been carried out for other fungal phytopatogens . Studies have been conducted on the influence of active substances and products, and the effects of active natural substances on fungal structure have been extensively reported . Similarly to the present study, conidial damage and conidial germination interference according to SEM data have been reported .…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Extensive structural SEM time‐course analysis of early infection steps has been carried out for other fungal phytopatogens . Studies have been conducted on the influence of active substances and products, and the effects of active natural substances on fungal structure have been extensively reported . Similarly to the present study, conidial damage and conidial germination interference according to SEM data have been reported .…”
Section: Resultsmentioning
confidence: 63%
“…These results support the possible action of TOH in solid substrates. Other studies have also demonstrated the ability of different EOs to prevent conidial germination, although these authors did not identify the chemical substance(s) that cause inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations